Design Principles for Peptide‐Amphiphile‐Induced Liposomal Receptor‐Targeting with Intracellular Thermosensitivity. Issue 1 (29th October 2015) - Shroff, Kamlesh; Liu, Dalong; Aravalli, Rajagopal N.; Forster, Colleen L.; Pengo, Thomas; Sanders, Mark A.; Ebbini, Emad S.; Kokkoli, Efrosini
Abstract: Thermosensitive stealth liposomes were created by mixing lipids and PEGylated lipids with single‐tail peptide‐amphiphiles. We demonstrated for the first time that the peptide‐amphiphiles provided receptor‐specific binding and cell internalization while inducing the thermosensitive properties of the liposomes. The formulations were stable at 37 °C in the presence of serum, with faster release of their encapsulated load at 41 °C compared to stealth liposomes without the peptide‐amphiphiles or commercially available thermosensitive stealth liposomes. The thermosensitive properties of our formulation were also examined in vivo. Preliminary work showed increased release of the encapsulated calcein after heating the liver of a mouse with a dual‐mode ultrasound array system for 20 s to 41–43 °C, 4 h after receiving tail vein injections of the liposomes, compared to a mouse that received the liposomal injections but no heating. The receptor‐targeting ability of the peptide‐functionalized liposomes was examined in vitro with MDA‐MB‐231 breast cancer cells. Our liposomes outperformed the other formulations as they showed specific binding, receptor‐mediated endocytosis, and increased intracellular temperature‐triggered release of encapsulated calcein. Abstract : Single‐tail peptide‐amphiphiles are responsible for receptor targeting and the thermosensitive properties of PEGylated liposomes. The peptide‐functionalized nanoparticles specifically bind to the receptor of choice, and after cell internalization they release their encapsulated load with temperature increase. They are stable in serum at 37 °C and exhibit fast release under mild hyperthermia at 41 °C in vitro and in vivo.